Financial Ratios as an Assessment tool for Measuring Supply Chain Performance and productivity: An Empirical Evidence from Industrial Bank of Iraq - Khetam Dekhn Hamzah; Batool Abd Ali Ghali; Gnan Abed kachi (International Journal of Supply Chain Management, 2019)
The present study is focused on the subject of financial analysis is one of the important topics in the field of financial management and accounting. The research hypothesis is achieved by not using the industrial bank for financial ratios. The low financial ratios listed in using the financial ratios and the focus of analysis of ratios for the five years. Which require reconsideration of the use of these ratios in the future by the bank. The results table of the use of financial ratios for the five years shown various importance. The data provided by the financial lists cannot be used for the purposes of planning and evaluating the efficiency of performance without using one of the means of financial analysis. The primary and secondary sources of data has been used for the present study and to make the analysis of the study more robust. The research aims at presenting a study represented by using the financial ratios for the purpose of evaluating performance efficiency. Financial analysis is considered one of the important tools in the business establishments and a basis of planning and control, which includes a detailed study of the data contained in the financial statements adopted by the project and the financial analysis by ratios is an important and fundamental means in the study of the financial position of the project in n light of the figures and data in its financial statements. The present also provide some policy level implications and also some future research directions are proposed to conclude the research study.